Induction of TLR-2 and TLR-5 expression by helicobacter pylori switches cagPAI-dependent signalling leading to the secretion of IL-8 and TNF-α - Pachathundikandi, Suneesh Kumar; Brandt, Sabine; Madassery, Joseph; Backert, Steffen (PLoS ONE, 2011)
Helicobacter pylori is the causative agent for developing gastritis, gastric ulcer, and even gastric cancer. Virulent strains carry the cag pathogenicity island (cagPAI) encoding a type-IV secretion system (T4SS) for injecting the CagA protein. However, mechanisms of sensing this pathogen through Toll-like receptors (TLRs) and downstream signalling pathways in the development of different pathologies are widely unclear. Here, we explored the involvement of TLR-2 and TLR-5 in THP-1 cells and HEK293 cell lines (stably transfected with TLR-2 or TLR-5) during infection with wild-type H. pylori and isogenic cagPAI mutants. H. pylori triggered enhanced TLR-2 and TLR-5 expression in THP-1, HEK293-TLR2 and HEK293-TLR5 cells, but not in the HEK293 control. In addition, IL-8 and TNF-α cytokine secretion in THP-1 cells was induced in a cagPAI-dependent manner. Furthermore, we show that HEK293 cells are not competent for the uptake of T4SS-delivered CagA, and are therefore ideally suited for studying TLR signalling in the absence of T4SS functions. HEK293 control cells, which do not induce TLR-2 and TLR-5 expression during infection, only secreted cytokines in small amounts, in agreement with T4SS functions being absent. In contrast, HEK293-TLR2 and HEK293-TLR5 cells were highly competent for inducing the secretion of IL-8 and TNF-α cytokines in a cagPAI-independent manner, suggesting that the expression of TLR-2 or TLR-5 has profoundly changed the capability to trigger pro-inflammatory signalling upon infection. Using phospho-specific antibodies and luciferase reporter assays, we further demonstrate that H. pylori induces IRAK-1 and IκB phosphorylation in a TLR-dependent manner, and this was required for activation of transcription factor NF-κB. Finally, NF-κB activation in HEK293-TLR2 and HEK293-TLR5 cells was confirmed by expressing p65-GFP which was translocated from the cytoplasm into the nucleus. These data indicate that H. pylori-induced expression of TLR-2 and TLR-5 can qualitatively shift cagPAI-dependent to cagPAI-independent pro-inflammatory signalling pathways with possible impact on the outcome of H. pylori-associated diseases. © 2011 Kumar Pachathundikandi et al.
Created from Fastlane, Scopus look-up